ZONAS MICROPALEONTOLOGICAS DEL OLIGOCENO DEL NORESTE DE MEXICO - MENESES DE GYVES, JAVIER (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1944)
Foraminfera are listed for each formation, and typical spp of the Anahuac and Vicksburg are figured
BOL ASOC MEX GEOL PET
Keywords: MICROPALEONTOLOGICAS, OLIGOCENO, MEXICO; CIENCIAS DE LA TIERRA Y DEL ESPACIO; GEOLOGIA; GEOLOGIA DEL PETROLEO